Current accounts in the eurozone countries: The role of euro, fiscal policies and financial developments - Jaromír Baxa; Tomáš Olešňaník (Charles University in Prague, Institute of Economic Studies (IES), 2014)
Should we blame the euro for widening of current account deficits in the EMU? In this paper, we employ time-specific fixed effect estimator to study determinants of the current account deficits of the EU countries before and after adoption of the euro. Our aim is to assess to what extent the increased current account deficits could be attributed to the single currency and to the role of other variables, especially fiscal policy and developments of financial sector. We show that euro had negative effect on current account balances of southern countries. Moreover, we provide evidence that the role of fiscal policy in current account dynamics changed with euro adoption and twin deficits emerged in many countries. Finally, we document significant role of growing credits to private sector for built-up of persistent current account deficits, hence the negative effects of excessive lending on external balance should be addressed by the regulators and policy makers in the future.
Keywords: E42; E62; F14; 330; current account; euro; fiscal balance; financial system